Pengaruh Estradiol Terhadap Sepsis - Haloho, Agustina Br.; Amin, Ramzi; Saleh, Mgs. Irsan; Murti, Krisna (Fakultas Kedokteran Universitas Trisakti, 2024)
Sepsis is an emergency condition as a result of host dysregulation systemic immune response to infection that is related to the end stage of organ dysfunction. Both sepsis and septic shock conditions are the main problems in ICU especially, those that affect millions of people in the whole world every year. Studies in line with immune-neuroendocrine related to sepsis get high attention about factors that play roles in sepsis pathogenesis and prognosis, like correlation to gender, hormones, and other factors. In this case, lots of experimental studies and clinical studies showed that sepsis has significant sexual dysmorphic. The female gender has proven protective against sepsis, meanwhile, males could have worse sepsis because of decreasing immunologic response that mediates cell and cardiovascular function. Estrogen is a hormone in women that plays important roles in not only reproductive function but also non-reproductive function. Physiological estrogen in women is divided into three forms: estrone (E1), estradiol (E2 or 17β- estradiol), and estriol (E3). Several experimental studies in animals showed that estradiol has a protective response when infection occurs. Estrogen generally stimulates cytokine release, induction of HO-1, and restoration of organ function due to sepsis. Potential pathogenesis for this condition is a specific expression of cytokine pro and anti-inflammation. This pathological inflammatory condition is related to gender that is found in surgical patients at the molecular level.